2021
DOI: 10.1021/acsami.0c21109
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Diblock DNA-Mediated Synthesis of Nanoflower-Shaped Photothermal Nanozymes for a Highly Sensitive Colorimetric Assay of Cancer Cells

Abstract: The activity of a nanozyme is closely related to its surface area-to-volume ratio and the surrounding temperature. To acquire highly active nanozymes, one-pot metallization-like synthesis of novel nanoflower-shaped photothermal nanostructures was conducted using polyadenine-containing diblock DNA as the scaffold. The nanoflower-shaped structures with a high surface area-to-volume ratio and photothermal performance exhibited excellent peroxidase-mimicking activity, and the biorecognition capability was retained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…[30][31][32] The essential of them is that only the ligand molecules or modification materials around the nanozymes are controlled by light for strengthening or weakening the catalytic activity, while the nanozymes themselves always hold the intrinsic property for catalysis. 33,34 In addition, unlike photocatalysis that happened over photoenzymes, in the above mentioned photo-controlled thermocatalytic systems, light is never be employed as the direct source of energy for driving the chemical conversion, although some nanomaterials (such as semiconductors and precious metal nanoparticles) are accompanied with photogeneration of reactive oxygen species under light stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] The essential of them is that only the ligand molecules or modification materials around the nanozymes are controlled by light for strengthening or weakening the catalytic activity, while the nanozymes themselves always hold the intrinsic property for catalysis. 33,34 In addition, unlike photocatalysis that happened over photoenzymes, in the above mentioned photo-controlled thermocatalytic systems, light is never be employed as the direct source of energy for driving the chemical conversion, although some nanomaterials (such as semiconductors and precious metal nanoparticles) are accompanied with photogeneration of reactive oxygen species under light stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they found that the length of DNA had little effect on the morphology of AgNPs. Subsequently, ssDNA sequences regulate the form of other shapes of metal nanoparticles (i.e., gold nanoflowers [64]), and bimetallic nanoparticles (i.e., Pd-Au bimetallic nanostructures [65]) have been reported.…”
Section: Dna Metallizationmentioning
confidence: 99%
“…Further, Au NPs have been used to detect target DNA or microRNA (miRNA) using complementary nucleic acids immobilized on Au NPs which then facilitated hybridization of the nucleic acids [ 32 , 33 ]. Au NPs also have been used to detect ions and cancer cells [ 34 , 35 ] further supporting the value of this nanozyme in biological applications.…”
Section: Nanozyme Classification and Their Catalytic Mechanismsmentioning
confidence: 99%